중환자 재활에서 물리치료사의 역할과 필요성 - 정경만; 최준완; 안창만; Kyeoung Man Jung; Jun-Wan Choi; Chang Man An (대한물리치료과학회지, 2023)
In the past, patients in the intensive care unit were mostly managed by the intensive care unit's own protocol through bed rest and sedation. The number of hospitalized patients in intensive care units in Korea is steadily increasing, but the mortality rate is higher than in developed countries and the perception of intensive care rehabilitation is lowered. The reality of intensive care rehabilitation in korea has many problems due to low fee structure, lack of manpower, and lack of policy establishment and will of related institutions. In addition, intensive care-rehabilitation should consist of a multidisciplinary tema, and the team composition should include professionals such as dedicated doctors, dedicated nurses, and physical therapists. Although the effect of intensive care unit rehabilitation has been confirmed through previous foreign studies, the reality of intensive care unit rehabilitation in Korea is currently lagging behind due to a system of low medical fees and the will of government agencies. This study was attempted to find out the role and necessity of physical therapists in intensive care rehabilitation so that rehabilitation medical fees suitable for reality can be set when domestic intensive care rehabilitation is institutionalized and activated in the future.